Impact of tumor dimensions and lymph node density on the survival of patients with hypopharyngeal squamous cell carcinoma - Ye LL; Rao J; Fan XW; Ji QH; Hu CS; Ying HM (Cancer Management and Research, 2018)
Lu-Lu Ye,1,2,* Jia Rao,2,3,* Xing-Wen Fan,1,2 Qing-Hai Ji,2,4 Chao-Su Hu,1,2 Hong-Mei Ying1,2 1Department of Radiation Oncology, Fudan University Shanghai Cancer Center, Shanghai 200032, P.R. China; 2Department of Oncology, Shanghai Medical College, Fudan University, Shanghai 200032, P.R. China; 3Department of Pathology, 4Department of Head and Neck Surgery, Fudan University Shanghai Cancer Center, Shanghai 200032, P.R. China *These authors contributed equally to this work Purpose: To analyze the potential variables affecting the survival of patients undergoing primary surgery for hypopharyngeal squamous cell carcinoma.Patients and methods: Between August 2007 and December 2016, 93 patients with primary hypopharyngeal squamous cell carcinomas undergoing radical surgery at Fudan University Shanghai Cancer Center were reviewed. The clinicopathological features were analyzed retrospectively. The optimal cutoff values were determined based on the receiver operating characteristic curve analysis. Pearson correlation coefficients were used to assess the correlations between variables. The Kaplan–Meier and Cox proportional hazard methods were used to evaluate the impact of variables on overall survival (OS), disease-specific survival (DSS), and disease-free survival (DFS).Results: Cox multivariate analysis revealed that a depth of invasion (DOI) ≥ 4.3 mm was correlated with inferior OS (P=0.045), DSS (P=0.046), and DFS (P=0.046). A primary tumor volume (PTV) ≥0.36 mL was related to poor OS (P=0.018), DSS (P=0.026), and DFS (P=0.036). A lymph node density (LND) ≥0.07 was also associated with worse OS (P=0.014) and DSS (P=0.045). Moreover, additional prognostic value was observed in the combined use of PTV and LND.Conclusion: The DOI, PTV, and LND obtained from the surgical specimens could provide additional valuable information for prognostic stratification and allowed the more appropriate selection of suitable candidates for more aggressive adjuvant therapy. Keywords: hypopharynx, surgery, depth of invasion, primary tumor volume, lymph node density, survival